Algoritmos diretos para sincronização de mediações e localização de faltas em linhas de transmissão com parâmetros elétricos desconhecidos - Monteiro, Roana d'Ávila Souza (2021)
In this work, angle synchronization and fault location methods are proposed, based on the fundamental frequency phasor approach, being independent of the electrical parameters of the transmission line and of iterative processes. In the proposed synchronization algorithm, the line capacitive effect is taken into account and only the analysis of steady-state voltage and current phasors is required, eliminating the need for settings based on line electrical parameters. In addition, it identifies angles in any quadrant and is insensitive to system operation conditions. Real operating scenarios of the Brazilian system are considered to assess the algorithm performance, including light, moderate and heavy line loading cases, and various power factors and line lengths. The obtained results show that the proposed synchronization solution is reliable, straightforward, and accurate, being useful for practical two-terminal phasor-based applications when traditional common time reference sources are not available. The tool developed for fault location requires pre and post-fault current and voltage phasors, being suitable for all types of faults (symmetrical and asymmetrical), and for transposed and untransposed transmission lines. The evaluation of the fault location algorithms is performed through fault simulations by the Alternative Transients Program (ATP) software. The obtained results prove the efficiency of the method in finding fault location with good precision.